Pengaruh Profitabilitas, Struktur Modal dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Kepemilikan Institusional sebagai Variabel Moderasi pada Perusahaan Consumer Non-Cyclicals di BEI (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effect of profitability, capital structure, and company size on company value, using institutional ownership as a moderating factor in companies from the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. Profitability will be assessed through Return on Equity (ROE), while capital structure will be evaluated using the Debt to Equity Ratio (DER). Company size will be determined by the natural logarithm of its total assets, company value will be measured by Price to Book Value (PBV), and institutional ownership will function as a moderating variable. A quantitative approach will be applied in this study, using multiple linear regression and Moderated Regression Analysis (MRA). The sample for this study includes 33 companies, so the total observations are 165. The findings of this study indicate that: (1) Profitability has a positive and significant effect on company value; (2) Capital structure and company size do not have a significant effect on company value; (3) Institutional ownership increases the relationship between profitability and company value; (4) Institutional ownership reduces the influence of capital structure on firm value; (5) Institutional ownership does not play a moderating role in the relationship between firm size and firm value.